Olfactory Communication of Sickness Cues in Respiratory Infection - Sarolidou, Georgia; Tognetti, Arnaud; Lasselin, Julie; Regenbogen, Christina; Lundström, Johan N.; Kimball, Bruce A.; Garke, Maria; Lekander, Mats; Axelsson, John; Olsson, Mats J. (Frontiers in Psychology, 2020)
Animal studies suggest that ill-health can be detected by way of body odor which, in turn, can be important information for the receiver to avoid potential infectious transmission from the sick individual. There are also a number of human observational studies that indicate that different types of disease are associated with more or less aversive smells. Recent studies have indicated that the body odor from otherwise healthy human individuals smell more aversive within a few hours as a function of a systemic inflammation of bacterial type induced by experimental exposure to an endotoxin (lipopolysaccharide). To investigate if naturally occurring immune activation also gives rise to perceivable olfactory changes, we collected body odor samples during five nights from individuals with a respiratory infection as well as when they were healthy. We hypothesized that independent raters would rate the body odor originating from sick individuals as smelling more aversive than when the same individuals were healthy. Even though body odor samples from sick individuals nominally smelled more intense, more disgusting, and less pleasant than the body odor from the same individuals when healthy, these effects were not statistically significant. Moreover, three questionnaires, Perceived Vulnerability to Disease, Disgust Scale, and Health Anxiety, were administered to the raters of the body odor to assess potential associations between sickness-related personality traits and body odor perception. No such association was found. Since experimentally induced inflammation have made body odors more aversive in previous studies, we discuss whether this difference between studies is due to the level of sickness or to the type of trigger of a sickness response.